Interactive Lecture Demonstrations (ILD) Model to Improve Students Understanding and Attitude towards Physics - Yani, Akhmad; Setiawan, Agus (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2022)
ILD learning design has been implemented to get an overview of improving in learning heat of understanding and the changing of attitude towards physics to student between a class that implemented ILD model with assisted science magic and a class that implemented ILD model without assisted science magic. The research method used was quasi experiment with nonequivalent pretest-posttest control group design. Two class of tenth grade were involved in this research 28, 26 students respectively experiment class and control class. The improvement of learning heat of understanding was calculated by the formula N gain based on the test data on the adaptation of Hake normalized and the changing of attitude towards physics by using CLASS questionnaire. The result show that gain average normalized Â on experiment class got 0.55 while on control class got 0.31. Based on different test the average on experiment class and control class at 95% confidence level (significant 0.05) this result show that ILD model with assisted science magic significantly improve materials of student understanding better than ILD model without assisted science magic. Based on student questionnaire, we found that the implementation of ILD model with assisted science magic result the changing of attitude towards physics better than ILD model without assisted science magic.